Synthesis of the ZnO-Ni0.5Zn0.5Fe2O4-Fe2O3 magnetic catalyst in pilot-scale by combustion reaction and its application on the biodiesel production process from oil residual - A.L. da Silva; A.F.F. Farias; J.R.M. Pontes; A.M. Rodrigues; A.C.F. de M. Costa (Arabian Journal of Chemistry, 2020)
A magnetic catalyst with composition ZnO-Ni0.5Zn0.5Fe2O4-Fe2O3 was synthesized by a combustion reaction on a pilot-scale and applied in the conversion of residual oil into biodiesel by simultaneous transesterification and esterification reactions (TES). For that, statistical analysis of the factors that influence the process (catalyst concentration, alcoholic route, and temperature) was evaluated by 23 factorial experimental design. The ZnO-Ni0.5Zn0.5Fe2O4-Fe2O3 magnetic catalyst was characterized in terms of the structure, morphology, magnetic, TPD-NH3 acidity analysis and catalytic properties. The results indicate the formation of a catalyst with a surface area of 52.9 m2g−1, and density of the sample was 4.8 g/cm3 which is consisted of a mixture of the phases containing 55.87% Fe2O3, 36.96% Ni0.5Zn0.5Fe2O4, and 7.16% ZnO. The magnetic characterization indicated that the synthesized catalyst is ferromagnetic with magnetization 6.12 emu/g and coercive field of 5.3 G. In the TES reactions, the residual oil was active showing conversion to 96.16% ethyl esters and with a long useful life maintaining sustained activity after two consecutive reuse cycles with the conversion of 95.27%, 93.07% and 76.93%, respectively. The experimental design was significant and presented a 95% reliability level. The statistical analysis identified (+1) and (−1) as higher and lower level variables, respectively. The amount of catalyst used was equal to 5%, at 200 °C in methyl alcohol (alcoholic route). In summary, a new catalyst composed of a mixture of magnetically active phases was developed and successfully applied in biodiesel’s synthesis from residual oil. Undoubtedly these results have a positive and significant impact on the environment and to society as a whole.